Elbow‐ and hinge‐bending motions of IgG: Dielectric response and dynamic feature. Issue 9 (September 2016) - Hayashi, Yoshihito; Yagihara, Shin
ABSTRACT: Immunoglobulin G (IgG) is a Y‐shaped globular protein consisting of two Fab segments connecting to an Fc segment with a flexible hinge region, in which the Fab segments show secondary flexibility at an "elbow" region. In the present work, the hinge‐bending and elbow‐bending motions of aqueous solutions of IgG by microwave dielectric measurements below the freezing point of bulk water was observed. The presence of unfreezable water around the macromolecules reduced the effects of steric hindrance normally generated by ice and enabled the intramolecular motions of IgG. At the same time, the overall IgG molecule rotation was restricted by ice. Papain digestion and reduction of the disulfide linkage at the hinge region was used to generate Fab and Fc fragments. In solutions of these fragments, the dielectric relaxation process of the hinge‐bending motion was absent, although the elbow‐bending motion remained. Three relaxation processes were observed for papain‐digested IgG. The high, middle, and low frequency processes were attributed to unfrozen water, local peptide motions cooperating with bound water, and the elbow‐bending motion, respectively. In the case of the intact IgG, an additional relaxation process due to the hinge‐bending motion was observed at frequencies lower than that of the elbow‐bending motion. © 2016 Wiley Periodicals, Inc. Biopolymers 105: 626–632, 2016.